Differences in Social Relationship Difficulties in Nursing Students - Warnidar, Eka; Hidayat, Fedri; Riani, Eka Oktarina; Oetama, Saiful; Elvin, Said Devi; Ritawati, Ritawati; Sufri, Sofyan; Faisal, T. Iskandar; Jamni, Teuku (Poltekkes Kemenkes Aceh, 2025)
Background: Difficulty in establishing social relationships is a significant issue that can negatively impact the psychological well-being of nursing students. Often feeling isolated, withdrawing from the social environment, and experiencing decreased academic motivation are difficulties that usually arise in students. Various factors contribute to this condition, including pressure to be accepted in certain social groups, such as trying to adjust appearance or behavior to be accepted by the environment, which actually triggers stress and identity crises. Understanding the background and causal factors to the differences in the level of social difficulties in nursing students is very important in efforts to improve psychological well-being and support the academic success of nursing students. Purpose: To determine the differences in social relationship difficulties in students at different levels of the diploma program in nursing. Methods: The study used an analytical survey design with a comparative approach. The research sample consisted of 642 respondents from students of the diploma program in nursing at Poltekkes Kemenkes Aceh and was obtained through a total sampling technique. The instrument used to measure the level of difficulty in social relationships was The Revised Cheek and Buss Shyness Scale (RCBS), which has been proven valid and reliable in measuring the level of individual personality. Data analysis was carried out using the Kruskal-Wallis test to compare differences in the level of difficulty in social relationships based on the group of variables studied. Results: Based on the results of statistical tests using the Kruskall Wallis test, it shows that the p-value is 0.01 (<0.05), which indicates that there is a significant difference in the average difficulty of social relationships in students between levels of the diploma program in nursing at Poltekkes Kemenkes Aceh. Conclusion: There is a significant difference in the level of difficulty of social relations between students based on the level of the diploma program in nursing at Poltekkes Kemenkes Aceh, which shows that the level of education is related to students' social adaptation abilities.